Processo de transição de uma banda civil para banda sinfônica - Samuel Mendonca Fagundes (2010)
This study aims to describe the transition process from a civilian band to a symphonic band. For this, the unit-case of study will be Banda Nossa Senhora do Carmo de Betim. It focuses more on aspects of their musical practice and the contents of its musical sounds as well as the social-cultural aspects involved in these practices. Observing the music as culture and, consequently, connecting it with the social relations that are established inside the musical group and also music group in the society in which operates. Therefore, it was done an ethnographic study whose theoretical framework is put in ethnomusicology. Social-cultural issues were addressed in order to comprehend the specific musical sound characteristics of the civil band and the symphonic band as being different because they are closely related to the production context and to the context of meaning and value on a scale that is not seen as absolute. Thus, in this study, the civil band and the symphonic band are considerate in their aesthetics and contextual differences. The band of Betim is in a process which aims its transformation to a symphonic band. The research presented here permitted a better comprehension of how this process is happening, so it was realized that the roots of the Betim band as a civil band influenced strongly in the transition, since changes in social meanings that are learned historically occur slowly. In this way, there is still an identification of the Betim Band with a musical practice of a civil band and the older musicians and the audiencethat knows this band for a long time, manifest a certain resistance to changes that have occurred as the change in repertoire and less participation in events and civic and religious festivities that that they have once participated because they sought to act according to the characteristics of a concert band. On the other hand, it already presents certain characteristics of a concert band, in other words, the Betim band wants to perform new roles. However, it is still an ongoing process